Athletic director's desk reference - Lopiano, Donna A. (Human Kinetics, 2014)
Loaded with practical tools, this resource guides programme administrators in navigating their increasingly complex roles in athletic programmes of any size. It includes more than 120 management tips and planning tools that provide expert insights and strategic advice